Population Increase and Vulnerability to Disasters In the Informal Settlements of Mwanza City, Tanzania (Tanzania Journal for Population studies and Development, 2011)
Urban population growth has demonstrated synergetic relationship with the growth of informal settlements and disasters. The increase in the number of people and their properties in informal settlements have accelerated the vulnerability of communities to disaster risks. This study employs Participatory Disaster Risk Assessment (PDRA) methodology to analyse vulnerability to disasters at household and community levels. Analysis and interpretation based on socio-economic and political ecology status of local community revealed that people living, and working in Mwanza city and their properties have been exposed to natural, human-made and human-induced hazards and disasters. The study revealed thatthesedisasters have threatened and destroyed the economies of poor households, both in terms of their frequency and severity of the damages.The study findings show that the future stability of Mwanza city ecosystem is on threat should the increased number of people and human activities on hazardous land persist. To improve quality of life and safety in the community prone to natural, human-made and human-induced disasters, there should be mitigation measures and strategies to reduce severity of disasters and to improve safety and security of people and their property. The study recommends that measures and strategies aimed at reducing disaster should address the whole set of issues leading to poverty and disparities within the community under the umbrella of neo-liberalism.